Lean Construction Waste Reduction Through the Autonomous Vehicle Technology - Owais, Omar A; Poshdar, Mani; GhaffarianHoseini, Ali; Ghaffarianhoseini, Amirhosein (International Group for Lean Construction, 2023)
In the automotive industry, autonomous vehicles (AVs) are an advanced innovation that has the potential to revolutionise the existing transportation system significantly. In addition, AVs provide benefits for society, the economy, and the environment. As far as Lean Construction (LC) is concerned, these features appear promising. LC's primary objective is to minimise the waste of resources, time, and effort. This study examines the potential contribution of AVs to LC through two exhaustive rounds of literature review. The research aims to establish the links between AVs and the overarching LC philosophy and principles. The first round of the literature review identified that AVs could reduce waste in three areas: inventory, transportation, and waiting time. Moreover, they can support solutions to environmental concerns. Additional literature reviews have identified five potential approaches for a new technology that can be applied to the construction industry to enhance the implementation of AVs. As well as the anticipated developments in each case are discussed accordingly. The practical implications of the findings are that AVs can reduce waste and cost, increase efficiency and productivity, and help create a more sustainable construction industry. According to the study, the construction industry should take a proactive approach to implementing AVs.
Keywords: Lean construction; AVs; transportation; waste